Effectiveness of Manual Vacuum Aspiration in the Management of Miscarriage and Retained Products of Conception - Ifat Balouch, Hina Akmal, Faryal Sardar, Zahida Parveen Brohi, Sabreena Talpur, Maryam Phulpoto, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the efficacy of manual vacuum aspiration (MVA) in terms of complications and complete uterine evacuation of the product of conception. Study design: Descriptive cross-sectional study. Place and duration: Department of Obstetrics and Gynecology, Bilawal Medical College, DHQ Hospital Kotri and CDF Hospital Hyderabad, from April 2020 to March 2021. Patient and method: All the patients with gestational of <14 weeks, and the diagnosis of missed miscarriage, blighted ovum, partial miscarriage, or RPOCs, who were undergone MVA was carried out. Primary outcome measures were efficacy and secondary outcome measures were to assess prevalence of complications including pain and cramps, infection and bleeding. Effectiveness was considered in terms of complete or incomplete evacuation. All the information was documented via a self-made study proforma. Results: A total of 83 patients were scheduled to undergo MVA. Majority of the cases 41.0% were presented with gestation age of 9 to 12 weeks. Most of the cases 56.6% had incomplete miscarriage, 31.3% were with missed miscarriage and 12.0% women had RPOCs. Mild to moderate pain and cramps were present in 91.60% of the cases, while only 6.0% of the cases had bleeding, and infection developed in 2 cases. According to effectiveness, complete evacuation was achieved in 81.9% of the cases. Conclusion: MVA is effective in the complete emptying of the uterine cavity and has high rates of acceptability and satisfaction. It reduces the waiting time for surgery, hospital stays, and GA complications. It is gradually gaining acceptability as a standard surgical procedure for safe early pregnancy termination. Keywords: Efficacy, safety, MVA, uterine evacuation, conception